The Tawen Myth as A Mechanism to Control Postpartum Maternal Health - Lanawati Lanawati; Ermeisi Er Unja; Margareta Martini (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Tawen myth is a traditional belief of the Dayak Ma’anyan community applied in postpartum care. It guides postpartum practices, during a period prone to stress due to physical changes, role shifts, and hormonal fluctuations, which can impact the psychological well-being of mothers. Objective to analyze the psychosocial impact of the Tawen myth on the mental well-being of postpartum mothers. A qualitative study involving 10 Dayak Ma’anyan women as primary informants, selected by purposive sampling, along with 4 cross-sectoral participants from village authorities, traditional leaders, healthcare providers, and village midwives. Data were gathered through in-depth interviews and field observations, analyzed using thematic analysis. Six themes emerged: 1) Reasons for practicing Itampadi within the Tawen myth, 2) The Tawen myth as a health control mechanism for postpartum mothers, 3) A mix of fear and calm as the emotional impact of the myth, 4) Social uncertainty, food limitations, and taboo violations as stressors, 5) Food restrictions reflecting deep concerns, 6) Physical and social activity limitations as preventive actions for Tawen. Psychosocial issues related to the Tawen myth stem from a combination of fear and calm in practicing Itampadi. Fear of Tawen strongly influences postpartum mothers to follow traditional practices. While these practices offer psychological security, they also create emotional pressure, especially in the face of social change and modern physical needs.